2001
DOI: 10.1046/j.1523-1755.2001.00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of living unrelated (commercial) renal transplantation

Abstract: Besides the ongoing ethical debate, commercial transplantation carries a high risk of unconventional complications, and despite that the patient survival rate is comparable, graft survival is worse than conventional living related transplantations at the midterm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 35 publications
9
54
0
3
Order By: Relevance
“…[30][31][32][33][34][35][36][37][38][39][40][41][42] In some studies, mostly those based on small data sets, patient survival and graft survival rates are considerably lower than the internationally accepted standard; in other studies, they are shown to be comparable with local results. Confounding factors -e.g.…”
Section: Consequences and Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33][34][35][36][37][38][39][40][41][42] In some studies, mostly those based on small data sets, patient survival and graft survival rates are considerably lower than the internationally accepted standard; in other studies, they are shown to be comparable with local results. Confounding factors -e.g.…”
Section: Consequences and Effectsmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38][39][40][41] Moreover, one study from the United Kingdom reports that patients who had been suspended from the local transplant list for medical reasons were operated on abroad. 33 These factors seem to indicate the existence of substandard medical practices.…”
Section: Consequences and Effectsmentioning
confidence: 99%
“…This high graft survival rate achieved with living donors sharing no HLA chromosomes with recipients shows that HLA incompatibility can be overcome by immunosuppression [25]. In one study from Alabama, Gaston et al [26] compared tripledrug therapy with guardable-drug therapy. noting that the immunosuppressive protocol did not affect graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…It is important that accurate data on outcomes of transplants carried out abroad are known so that patients can be counselled about such activity [24,42] . The outcome of recipients of organs through TT is reported to be inferior to those transplanted under ethically more acceptable conditions (Table 2) [5,6,23,25,[41][42][43][44][45][46][47][48][49][50][51][52][53][54] .…”
Section: Transplant Outcomementioning
confidence: 99%
“…Transplants performed in less than ideal circumstances are characterised by inadequate pretransplant evaluation, general lack of information about peri-operative issues, immunosuppression and long term outcome. Despite these factors, there are numerous reports indicating that TT is associated with a high incidence of surgical complications, acute rejection and invasive infection which cause major morbidity and mortality [5,23,25,29,43,44,46,49,50,51,[55][56][57][58] .…”
Section: Transplant Outcomementioning
confidence: 99%